2021
DOI: 10.3389/fimmu.2021.715098
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus rhamnosus GR-1 Prevents Escherichia coli-Induced Apoptosis Through PINK1/Parkin-Mediated Mitophagy in Bovine Mastitis

Abstract: Escherichia coli is one of the most important pathogens that cause clinical mastitis in dairy cattle worldwide and lead to severe economic losses. Antibiotics are often used to treat this inflammatory disease; however, antimicrobial resistance and environmental pollution cannot be ignored. Probiotic is the best alternative; however, its mechanisms of action to prevent mastitis remain unclear. Moreover, the role of probiotics in regulating mitophagy, a selective autophagy that maintains mitochondrial quality, n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…The beneficial effects of a direct modulation of NLRP3 were also confirmed by a downregulation of pro-inflammatory cytokines, upregulation of anti-inflammatory players. These results have been also described feeding animals or treating cells derived from livestock with probiotics (1 × 10 5 CFU of Lactobacillus rhamnosus GR-1 and 3 × 10 5 –2 × 10 7 CFU of Lactobacillus johnsonii L531) with the aim of limiting the inflammatory damage of bacterial infections induced by Escherichia coli in porcine mammary epithelial cells, MAC-T cells and in a mouse mastitis model, or Salmonella typhimurium in IPEC-J2 cells [ 184 , 185 , 186 ]. The administration of these probiotics allowed limited bacterial adhesion to cells and bacterial alteration of cellular morphology, thus removing the first cause of ROS production and immune system activation.…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…The beneficial effects of a direct modulation of NLRP3 were also confirmed by a downregulation of pro-inflammatory cytokines, upregulation of anti-inflammatory players. These results have been also described feeding animals or treating cells derived from livestock with probiotics (1 × 10 5 CFU of Lactobacillus rhamnosus GR-1 and 3 × 10 5 –2 × 10 7 CFU of Lactobacillus johnsonii L531) with the aim of limiting the inflammatory damage of bacterial infections induced by Escherichia coli in porcine mammary epithelial cells, MAC-T cells and in a mouse mastitis model, or Salmonella typhimurium in IPEC-J2 cells [ 184 , 185 , 186 ]. The administration of these probiotics allowed limited bacterial adhesion to cells and bacterial alteration of cellular morphology, thus removing the first cause of ROS production and immune system activation.…”
Section: Food Components As Nlpr3 Modulatorsmentioning
confidence: 99%
“…lactis was isolated from feces of healthy pigs and it was grown in De Man, Rogosa, and Sharpe (MRS, Oxoid, Hampshire, UK) broth supplemented with 0.2% L-cysteine and 5% equine serum for 36 h at 37 • C under the anaerobic condition. Escherichia coli strain O111:K58 (CVCC1450; China Institute of Veterinary Drug Center, Beijing, China) was grown in Luria-Bertani (LB, Oxoid, Basingstoke, England) broth at 37 • C with constant shaking, until reaching the mid-log phase [28].…”
Section: Bacterial Strains and Preparation Of Conditioned Mediamentioning
confidence: 99%
“…Mitochondrial dysfunction could result in ROS release into the cytosol and mitophagy occurs to optimize clearance of abnormal mitochondria to decrease ROS accumulation in the cytosol ( 38 ). The production of ROS could be inhibited by mitophagy in Influenza viruses and Escherichia infection ( 18 , 39 41 ). In agreement with previous studies, our study revealed that promoting mitophagy could reduce the production of ROS in N. caninum infection, while inhibiting mitophagy up-regulated ROS production.…”
Section: Discussionmentioning
confidence: 99%